MISREPRESENTATION OF ISLAM IN MENTEGA TERBANG: A NARRATIVE ANALYSIS - Mohd Sofian, Muhammad Raqib; Ahmad Sabri, Safiyyah; Mustafa, Muhamad Zaki; Firly Annisa; Frizki Yulianti Nurnisya (PT ANTIS INTERNATIONAL PUBLISHER, 2025)
Objective: This study investigates the misrepresentation of Islam in the controversial Malaysian film Mentega Terbang through a detailed narrative analysis. The film, centered on a young Muslim girl's spiritual exploration and questioning of religious boundaries, has ignited significant public discourse and backlash, particularly within Muslim communities. The objective is to examine how Mentega Terbang portrays Islamic values, beliefs, and practices, and to identify elements within the narrative that may challenge or contradict mainstream Islamic teachings. Method: A qualitative narrative analysis was employed to examine the film’s storyline, character development, dialogue, and symbolism. This approach enabled the identification of underlying messages and potential misrepresentations related to Islamic principles. Results: The findings reveal that Mentega Terbang presents a complex and sometimes conflicting depiction of Islam, often deviating from established religious teachings. These portrayals may contribute to misunderstandings and reinforce negative perceptions among viewers. Novelty: This study offers a nuanced perspective on media representation of religion in Malaysia, highlighting how cinematic narratives can influence public perceptions of Islam. It contributes to media and religious studies by addressing the gap in understanding how fictional media shapes interfaith understanding in multicultural Muslim-majority societies. Recommendations are offered for responsible religious representation in film.